2007
DOI: 10.1590/s0103-90162007000600009
|View full text |Cite
|
Sign up to set email alerts
|

Rates of calcium, yield and quality of snap bean

Abstract: Calcium ions (Ca) play an important role in many biochemical processes, delaying senescence and controlling physiological disorders in fruits and vegetables. The objective of this experiment was to analyze the effect of increasing calcium concentrations in snap beans. Snap bean cultivar UEL 1 was sown in sand containing 80 mg L -1 of calcium supplemented with nutrient solution, plus calcium at different contents: 0, 75, 150 and 300 mg L -1 . Ca was mainly recovered in the shoots, followed by roots and pods. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
3
5
0
1
Order By: Relevance
“…For the other lines, the increase in calcium concentration in the nutrient solution did not increase the dry mass of pods. Similar results were obtained by Favaro et al (2007) in snap beans.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For the other lines, the increase in calcium concentration in the nutrient solution did not increase the dry mass of pods. Similar results were obtained by Favaro et al (2007) in snap beans.…”
Section: Resultssupporting
confidence: 89%
“…The high calcium concentration in the nutrient solution increased the mean value for number of pods and of grains per plant, number grains per pod and grain yield (Table 1). Similar effects were recorded by Favaro et al (2007) in number of green pods on snap bean plants grown in the high calcium concentration in the nutrient solution at 10 to 12 days after anthesis of flowers. Such effect has been attributed to low abortion of flowers and pods, because pollen germination and pollen tube growth is enhanced by calcium (GE; TIAN; RUSSEL, 2007).…”
Section: Resultssupporting
confidence: 77%
“…In this sense, Favaro et al (2007) found that Ca 2+ concentration in solution improves biomass production in snap bean. In our experiment P enhanced Ca 2+ assimilation, with an important Ca 2+ presence in edible organs, improving green bean quality for human nutrition.…”
Section: Resultsmentioning
confidence: 95%
“…The deficiencies caused by nutrients imbalance may reflect in lower photosynthetic efficiency, leaf area reduction, photosynthetic pigment content, among other alterations. These changes lead to a poor tissue formation, early senescence, and lower plant development, negatively influencing dry matter production [2] [5]. No studies on macronutrient omission in snap bean have been found, although this species has specific characteristics that can modify the physiological and nutritional mechanisms when subjected to nutritional deficiency.…”
Section: Introductionmentioning
confidence: 99%